Geopolitik Indonesia dalam pusaran Indo-Pasifik: Tantangan dan strategi nasional - Muzammil, Muhammad Gholid (Maliki Interdisciplinary Journal, 2026)
This article examines Indonesia’s strategic position within the increasingly competitive geopolitical dynamics of the Indo-Pacific region. As the world’s largest archipelagic state located between two oceans and two continents, Indonesia faces complex challenges, including great power rivalry, territorial disputes, maritime security threats, and global economic and technological pressures. This study aims to analyze these key challenges while formulating adaptive and sustainable national strategies. The research employs a qualitative approach through literature review and policy analysis. The findings indicate that Indonesia must strengthen its active diplomacy, particularly through ASEAN, safeguard its maritime sovereignty, and enhance defense and maritime security capabilities. Furthermore, strengthening the national economy through improved connectivity and energy resilience is crucial in addressing global uncertainties. Indonesia’s strategy should also emphasize its “free and active” foreign policy by maintaining a balanced relationship among major powers without being drawn into conflict. By doing so, Indonesia can maximize regional cooperation opportunities while minimizing geopolitical risks. Ultimately, Indonesia’s ability to navigate Indo-Pacific dynamics will determine its role as a stabilizing force and a key actor in shaping a peaceful, inclusive, and cooperative regional order.